Assessment of Soil Conservation Efficiencies of Selected Medicinal and Aromatic Plants in Nilgiris - Singh, D. V.; Sikka, A. K.; Madhu, M.; Chand, Subhash; Henry, C. (Indian Forester, 2004)
A study was conducted to quantify runoff and soil loss under the cultivation of prominent medicinal and aromatic plants in the high hills of Nilgiris, in order to assess their relative soil and water conservation efficiencies. Six species, namely Geranium (Pelargonium graveolens), Rosemary (Rosmarinus officinalis) , Cineraria (Ceneraria maritima), Thyme (Thymus vulgaris), Mentha (Mentha piperita) and Digitalis (Digitalis purpurea) were planted in 15 m Ã— 5 m plots on 15 percent land slope. Geranium recorded highest average green biomass yield followed by Digitalis, Cineraria, Mentha and Rosemary. Runoff and soil loss was maximum under Thyme followed by Cineraria because of their poor canopy cover. The lowest average annual soil loss and run off, over four years, was observed from Digitalis followed by Mentha and Geranium due to their quick establishment and higher canopy coverage. Relative Soil and Water Conservation Efficiency (RSWCE) varied from 36.4 per cent under Cineraria to 96.6 percent under Digitalis with Mentha, Geranium and Rosemary registering RSWCE of 95.1, 88.4 and 87.8 percent, respectively. It is suggested that Digitalis, Mentha, Geranium and Rosemary cultivation could be the best options for a diversified land use system as well as for cover crop, intercrop and vegetative barrier in the Nilgiris for effective soil conservation.